(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2025)
Purpose: The aim of this paper is to investigate the occurrence and characteristics of hybrid organizations in the Croatian construction industry and their impact on operational flexibility and enterprise performance. Methodology: The characteristics of hybrid organizations were described through the following variables: “Relational Governance” (RM), “Level of Information Sharing” (LIS), and “Subcontractor Network Design” (SND). Their significance is tested by a regression model of relationships with target variables “Operational Flexibility” (OF) and “Enterprise Performance” (EP). A total of 137 construction enterprises in Croatia participated in the research. Results: The significant positive impact of “Relational Governance” (RG) and “Subcontractor Network Design” (SND) on “Operational Flexibility” (OF) is observed. Furthermore, the significant positive impact of “Level of Information Sharing” (LIS) on “Subcontractor Network Design” (SND) is observed in a subsequently set regression model. Conclusion: The results of the analysis indicate that Croatian construction companies create long-lasting hybrid organizations with their subcontractors. These organizations are significantly based on a mechanism of collaboration, which proves to be key to operational flexibility in achieving good business performance.